Method for producing laminated foam sheet and extruded laminated foam sheet

Through the coextrusion layering law, the combination of polyethylene and ionomer resin is used to solve the antistatic and pollution problems of laminated foam sheets, and the production of laminated foam sheets with high efficiency antistatic properties and low pollution effect is achieved. .

CN116215034BActive Publication Date: 2024-12-13JSP CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310225944.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-28
Filing Date
2020-02-04
Publication Date
2024-12-13
Estimated Expiration
2040-02-04

AI Technical Summary

Technical Problem

The prior art is difficult to legally generate laminated foam sheets with excellent antistatic properties through coextrusion layers, and laminated foam sheets are prone to contamination of low molecular substances in applications.

Method used

By using a coextrusion method of polyethylene-based resin and ionomer resin, a laminated foam sheet with an antistatic layer is formed by providing a melt containing a physical foaming agent and a volatile plasticizer to ensure the antistatic layer. The uniform dispersion and excellent properties of the components are adjusted and the molar ratio is controlled, and the melt flow rate and melting point difference value are achieved.

Benefits of technology

It has successfully produced laminated foam sheets with excellent antistatic properties and pollution prevention, with low surface resistivity and uniform dispersion phases, suitable as buffer material for sandwich sheets and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116215034B_ABST
    Figure CN116215034B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for producing a laminated foam sheet and an extruded laminated foam sheet. The laminated foam sheet having a polyethylene resin foam layer and a polyethylene antistatic layer laminated on one or both sides thereof is produced by coextruding melts for the respective layers, wherein the melt for the antistatic layer contains a polyethylene resin, an ionomer resin antistatic agent and a specific amount of a volatile plasticizer blend containing an alcohol and a saturated hydrocarbon or a dialkyl ether. The antistatic layer of the obtained laminated foam sheet has a specific morphology.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an invention patent application. The application date of the parent application is February 4, 2020, the application number is 202010079719.4, and the name of the invention is "Method for producing laminated foam sheets and extruding laminated foam sheets". Technical Field

[0002] The present invention relates to a method for producing laminated foam sheets and to extruded antistatic laminated foam sheets. Background Art

[0003] Polyethylene-based resin foam sheets are soft and flexible, and have good cushioning properties. They are now widely used as interlayer sheets inserted between glass plates (such as liquid crystal panels), and cushioning or packaging materials for electronic devices. Because such foam sheets are prone to static electricity and cause dust deposition problems, they must be given antistatic properties. In order to solve the above problems, Japanese Patent Publication No. JP-A-2016-204227 proposes a method for producing a laminated foam sheet, wherein a melt for forming a foam layer and a melt for forming a resin layer containing a polymer antistatic agent are coextruded to obtain a laminated foam sheet having a foam layer covered by an antistatic resin layer.

[0004] For use as an interlayer sheet for glass and the like, there is a strong demand for laminated foam sheets showing greatly improved properties for preventing articles to be packaged or wrapped with the sheets from being contaminated by low molecular weight substances contained therein. Therefore, it has been proposed to use ionomer resins having a relatively low content of low molecular weight substances as polymeric antistatic agents.

[0005] The present inventors have found that laminating an ionomer-containing polyethylene resin layer on a polyethylene resin foam layer by coextrusion lamination encounters difficulties in developing the desired antistatic properties in a stable manner.

[0006] An object of the present invention is to provide a method for producing a laminated foam sheet, which is capable of producing a laminated foam sheet having desired antistatic properties using an ionomer resin as a polymer antistatic agent by a coextrusion lamination method. Another object of the present invention is to provide a novel laminated foam sheet, which exhibits excellent antistatic properties and also has an excellent property of preventing articles to be packaged or wrapped with the sheet from being contaminated by low molecular substances contained in the sheet. Summary of the invention

[0007] According to one aspect of the present invention, the following method is provided:

[0008] [1] A method for producing a laminated foam sheet having a polyethylene-based resin foam layer and a polyethylene-based resin antistatic layer laminated on at least one side of the foam layer, the method comprising the steps of:

[0009] providing a first melt containing a polyethylene-based resin (PE-1) and a physical foaming agent,

[0010] providing a second melt containing a polyethylene-based resin (PE-2), an ionomer resin as a polymeric antistatic agent, and a volatile plasticizer, and

[0011] co-extruding the first melt and the second melt to form a laminated foam sheet, wherein the polyethylene-based resin foam layer and the polyethylene-based resin antistatic layer are formed from the first melt and the second melt, respectively,

[0012] wherein the volatile plasticizer consists of a blend of component (A) and component (B), wherein component (A) is at least one alcohol having a boiling point of 120° C. or less, and component (B) is at least one selected from the group consisting of a saturated hydrocarbon having 3 to 5 carbon atoms, and a dialkyl ether in which the alkyl groups each have 1 to 3 carbon atoms,

[0013] wherein the molar ratio of component (A) to component (B) is 5:95 to 95:5, and

[0014] The volatile plasticizer is present in the second melt in an amount of 0.1 to 10 moles per kilogram of the total weight of the polyethylene-based resin (PE-2) and the ionomer resin.

[0015] [2] The method according to the above-mentioned [1], wherein the ionomer resin is present in the second melt in an amount of 1 to 80% by weight based on the total weight of the polyethylene-based resin (PE-2) and the ionomer resin.

[0016] [3] The method according to [1] or [2] above, wherein component (A) contains ethanol in an amount of 50% by weight or more based on the weight of component (A).

[0017] [4] The method according to any one of [1] to [3] above, wherein component (A) is present in the second melt in an amount of 1 to 25 mol per kg of the ionomer resin.

[0018] [5] The method according to any one of [1] to [4] above, wherein the ionomer resin has a melt flow rate of 3 g / 10 min or less at a temperature of 190° C. and a load of 2.16 kg.

[0019] [6] The method according to any one of [1] to [5] above, wherein the polyethylene-based resin (PE-2) has a melt flow rate of 1 to 20 g / 10 min at a temperature of 190° C. and a load of 2.16 kg.

[0020] [7] The method according to any one of [1] to [6] above, wherein the laminated foam sheet has a mass fraction of 20 to 200 kg / m 3 The apparent density of .

[0021] In another aspect, the present invention provides the following laminated foam sheet:

[0022] [8] An extrusion laminated foam sheet comprising a polyethylene-based resin foam layer and a polyethylene-based resin antistatic layer, the antistatic layer being laminated on at least one side of the foam layer and containing a polyethylene-based resin (PE-2) and an ionomer resin as a polymer antistatic agent,

[0023] wherein the polyethylene-based resin (PE-2) forms a continuous phase, and the ionomer resin forms a dispersed phase dispersed in the continuous phase, and

[0024] The number-based median value S of the cross-sectional area of ​​the dispersed phase on the vertical cross section of the antistatic layer taken along the extrusion direction of the laminated foam sheet is 50 1×10 2 Up to 1×10 6 nm 2 , and the median value LM of the diameter of the dispersed phase in the extrusion direction 50 The median value of the diameter of the dispersed phase in the thickness direction LT 50 The ratio LM 50 / LT 50 2 or higher.

[0025] [9] An extruded laminated foam sheet according to [8] above, wherein the average number NT of dispersed phases intersecting with a vertical line segment extending between both sides of the antistatic layer on a vertical cross section of the antistatic layer taken along the extrusion direction of the laminated foam sheet is 1 or more.

[0026]

[10] The extruded laminated foam sheet according to [8] or [9] above, wherein the antistatic layer has 1×10 12 Ω or lower surface resistivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Other objects, features and advantages of the present invention will become apparent from the following detailed description of preferred embodiments of the present invention when considered in light of the accompanying drawings, in which:

[0028] Figure 1 is a transmission electron micrograph (magnification 7,000) of a vertical cross section of the antistatic layer taken along the extrusion direction of the extrusion laminated foam sheet obtained in Example 9;

[0029] Figure 2is a transmission electron micrograph (magnification 70,000) of a vertical cross section of the antistatic layer taken along the extrusion direction of the extrusion laminated foam sheet obtained in Example 9; and

[0030] Figure 3 is a transmission electron micrograph of a vertical cross section of the antistatic layer taken along the extrusion direction of the extrusion laminated foam sheet obtained in Comparative Example 3 (magnification: 7,000). DETAILED DESCRIPTION

[0031] The method for producing a laminated foam sheet according to the present invention comprises: providing a first melt containing a polyethylene-based resin (PE-1) and a physical foaming agent, and providing a second melt containing a polyethylene-based resin (PE-2) and an ionomer resin (which acts as a polymer antistatic agent) and a volatile plasticizer. The first melt and the second melt are then co-extruded to form a laminated foam sheet, wherein the first melt forms a polyethylene-based resin foam layer, and the second melt forms an antistatic layer disposed on at least one side of the foam layer.

[0032] More specifically, the polyethylene-based resin PE-1 is fed into the extruder and heated and kneaded, and a physical foaming agent is injected therein. The resulting mixture is further kneaded to obtain the first melt for forming a foam layer. Meanwhile, the polyethylene-based resin PE-2 and ionomer resin polymer antistatic agent are fed into another extruder and heated and kneaded, and a volatile plasticizer is injected therein. The resulting mixture is further kneaded to obtain the second melt for forming an antistatic layer. The first melt thus obtained and the second melt are fed into the coextrusion die head, and coextruded into a lower pressure environment (usually to the atmosphere) by the die head, expand it. It goes without saying that when the antistatic layer is laminated on the two sides of the foam layer, and when the respective compositions of two antistatic layers are different from each other, it is necessary to use different types of melts to form different antistatic layers.

[0033] Next, the polyethylene-based resin (PE-1) used in the first melt for forming the foam layer is described. The polyethylene-based resin (PE-1) can be, for example, low-density polyethylene, very low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and a mixture of two or more of these olefinic polymers and copolymers.

[0034] It is preferred that the polyethylene-based resin (PE-1) contains low-density polyethylene in an amount of 50 wt % or more, more preferably 60 wt % or more, still more preferably 80 wt % or more, particularly preferably 90 wt % or more. The low-density polyethylene is a polyethylene having a density of 910 kg / m 3or higher and lower than 930kg / m 3 Olefinic polymers.

[0035] If desired, the polyethylene-based resin (PE-1) may contain one or more additional polymers other than the olefinic polymer, such as thermoplastic elastomers and thermoplastic resins. Such additional polymers are preferably used in an amount of 20 wt% or less, more preferably 10 wt% or less, based on the weight of the polyethylene-based resin (PE-1). The polyethylene-based resin (PE-1) is preferably substantially free of such additional polymers.

[0036] From the viewpoint of extrusion foamability, it is preferred that the polyethylene-based resin (PE-1) has a melt flow rate (MFR) of 0.5 to 15 g / 10 min. As used herein, MFR is measured at a temperature of 190° C. and a load of 2.16 kg according to JIS K7210-1 (2014).

[0037] For good extrusion foaming properties and the ability to form a foam layer with excellent cushioning properties, it is also preferred that the polyethylene-based resin (PE-1) has a melting point (Tmp1) of 100 to 135°C, more preferably 100 to 130°C, still more preferably 100 to 120°C, and particularly preferably 100 to 115°C.

[0038] The melting point (Tmp1) is measured by heat flow differential scanning calorimetry according to JIS K7121 (1987). More specifically, after the specimen is subjected to a pretreatment (conditioning treatment) according to "3. Pretreatment of test sample (2)" of JIS K7121 (1987) (cooling rate of 10°C / min), the melting point is measured at a heating rate of 10°C / min. The peak top temperature of the measured melting peak is the melting point (Tmp1). When there are two or more melting peaks in the DSC curve, the peak top temperature of the melting peak with the largest area is the melting point (Tmp1).

[0039] In addition to the polyethylene-based resin (PE-1), the first melt for forming the foam layer may also contain one or more additives such as cell control agents, nucleating agents, antioxidants, heat stabilizers, weather stabilizers, UV absorbers, flame retardants, antibacterial agents, anti-shrinkage agents and inorganic fillers.

[0040] Next will describe the polyethylene-based resin (PE-2) and ionomer resin contained in the second melt for forming the antistatic layer.Polyethylene-based resin (PE-2) can be selected from the olefinic polymer described above about the described polyethylene-based resin (PE-1), and from the viewpoint of softness and pliability, preferably contain low density polyethylene with 50 % by weight or higher, more preferably 60 % by weight or higher, more preferably 80 % by weight or higher, particularly preferably 90 % by weight or higher amount.For the close combination between foam layer and the antistatic layer, preferably the olefinic polymer of the same kind is used for polyethylene-based resin (PE-1) and (PE-2).

[0041] The polyethylene-based resin (PE-2) may contain one or more additional resins, such as thermoplastic resins other than olefinic polymers. Such additional resins are preferably added in an amount of 20% by weight or less, more preferably 10% by weight or less, based on the total weight of the polyethylene-based resin (PE-2) and the ionomer resin described below. However, for improved cushioning properties and recyclability of the laminated foam sheet, it is preferred that the polyethylene-based resin (PE-2) is substantially free of polystyrene-based resins, such as general-purpose polystyrene, rubber-modified polystyrene (impact polystyrene) and copolymers of styrene and copolymerizable vinyl monomers. The content of such styrene-based resins in the second melt should be less than 5% by weight or less, preferably 3% by weight or less, particularly preferably zero, based on the total weight of the polyethylene-based resin (PE-2) and the ionomer resin described below.

[0042] In the method of the present invention, an ionomer resin is used as a polymer antistatic agent. Such ionomer resins used as antistatic ionomer resins will be simply referred to as "ionomer resins". Ionomer resins are polymers containing interchain ionic bonds and can be obtained by copolymerizing ethylene and unsaturated carboxylic acids, followed by neutralization by metal cations. Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid and maleic acid. Examples of metal cations include lithium, sodium, potassium and calcium. Potassium-containing ionomer resins are particularly preferred. Ionomer resins have low surface resistivity and are able to impart the desired antistatic properties to laminated foam sheets. In addition, because the ionomer resin has a low content of low molecular weight substances, surface contamination of articles in direct contact with the laminated foam sheet containing the ionomer is prevented due to the transfer of low molecular weight substances from the laminated foam sheet.

[0043] In order to obtain a laminated foam sheet having the desired antistatic properties in a stable manner, the ionomer resin preferably has a 1×10 12 Ω or less. For this reason, the surface resistivity of the ionomer resin is more preferably 1×10 11 Ω or less, and more preferably 1×10 10Ω or less, particularly preferably 1×10 9 Ω or less. The surface resistivity is measured in accordance with JIS K6271 (2001). In this case, the ionomer resin is heat-pressed at a temperature of 200° C. to form a sheet having a thickness of about 0.1 mm. A test piece is cut out from the obtained sheet, and the surface resistivity of the ionomer resin is measured.

[0044] In order that low molecular weight substances which may be contained in the ionomer resin show less tendency to migrate from the laminated foam sheet to the article to be in contact therewith, the ionomer resin preferably has a melt flow rate MFR of 10 g / 10 min or less, more preferably 7 g / 10 min or less, and still more preferably 3 g / 10 min at a temperature of 190° C. and a load of 2.16 kg. I .MFR I The lower limit is about 1 g / 10 min.

[0045] In order to form an antistatic layer in a stable manner by coextrusion lamination, the polyethylene-based resin (PE-2) preferably has a melt flow rate MFR of 1 to 20 g / 10 min, more preferably 5 to 15 g / 10 min, at a temperature of 190° C. and a load of 2.16 kg. E The preferred melt flow rate MFR of the polyethylene-based resin (PE-2) is E Equal to or greater than the melt flow rate of the polyethylene-based resin (PE-1) of the foam layer.

[0046] From the viewpoint of the dispersibility of the ionomer resin in the antistatic layer, it is preferred that the melt flow rate MFR of the polyethylene-based resin (PE-2) is E MFR of ionomer resin I The difference between E -MFR I ) is 5 to 20 g / 10 min, more preferably 6 to 15 g / 10 min, and particularly preferably 6 to 12 g / 10 min. Although when the coextrusion temperature is low to form a suitable foam layer, the difference (MFR E -MFR I ) generally leads to coextrusion difficulties, but the process of the present invention (as described below, in which a specific volatile plasticizer is incorporated into the second melt to form an antistatic layer) can easily produce a laminated foam sheet having excellent antistatic properties in a stable manner even when the difference (MFR E -MFR I ) is within the above range.

[0047] In order to achieve the desired lamination between the foam layer and the antistatic layer, the antistatic layer becomes uniform, and the laminated foam sheet shows uniform antistatic properties over the entire surface, the polyethylene-based resin (PE-2) preferably has a melting point of 100 to 135°C, more preferably 100 to 130°C, still more preferably 100 to 120°C, particularly preferably 100 to 115°C.

[0048] It is preferred that the difference (Tmp-Tmi) between the melting point Tmp of the polyethylene-based resin (PE-2) and the melting point Tmi of the ionomer is 5 to 45°C. When the difference (Tmp-Tmi) falls within the above range, and when a specific volatile plasticizer is incorporated into the second melt as described below to form an antistatic layer, the ionomer resin can be easily and appropriately dispersed in the matrix of the polyethylene-based resin (PE-2), even when the melting point of the polyethylene-based resin (PE-1) is made low for the purpose of forming a suitable foam layer, and further, even when the melting point of the polyethylene-based resin (PE-2) is made low so as to match the melting point of the foam layer. From this viewpoint, the difference (Tmp-Tmi) is more preferably 8 to 35°C, still more preferably 10 to 30°C, particularly preferably 10 to 25°C. The melting point Tmi of the ionomer is preferably about 80 to 110°C, more preferably 85°C to 100°C.

[0049] The melting points Tmp and Tmi are measured by heat flow type differential scanning calorimeter measurement in accordance with JIS K7121 (1987) in the same manner as previously described with respect to the polyethylene-based resin (PE-1).

[0050] Specific examples of the ionomer resin include those available from duPont-Mitsui Polychemicals Co., Ltd. under the trade names of "ENTIRA SD100" and "ENTIRA MK400".

[0051] In order for the obtained laminated foam sheet to have excellent flexibility and to exhibit the desired antistatic properties, the ionomer resin is preferably contained in the second melt for forming the antistatic layer in an amount of 1 to 80 wt % based on the total weight (100 wt %) of the polyethylene-based resin (PE-2) and the ionomer resin. From this viewpoint, the lower limit of the amount of the ionomer resin is more preferably 5 wt %, further preferably 8 wt %, particularly preferably 10 wt %, while the upper limit thereof is more preferably 60 wt %, further more preferably 50 wt %, still further more preferably 30 wt %, particularly preferably 20 wt %.

[0052] Next, the volatile plasticizer contained in the second melt for forming the antistatic layer together with the polyethylene-based resin (PE-2) and the ionomer will be described. The volatile plasticizer is composed of a blend of component (A) and component (B), wherein component (A) is at least one alcohol having a boiling point of 120° C. or less, and component (B) is at least one selected from the group consisting of saturated hydrocarbons having 3 to 5 carbon atoms, and dialkyl ethers in which the alkyl groups each have 1 to 3 carbon atoms.

[0053] The method of the present invention allows the foam layer and the antistatic layer to be laminated in a stable manner due to the presence of a specific volatile plasticizer in the second melt used to form the ionomer-containing antistatic layer. Although not wishing to be bound by theory, it is inferred that the above effect is achieved by the following mechanism.

[0054] Ionomer resin is a polymer having a pseudo cross-linked structure in which metal cations and carboxylic acid groups are ionically bonded. The melt viscosity of the ionomer resin is greatly affected by temperature. At high temperatures, the melt viscosity of the molten ionomer resin decreases. When the temperature of the molten ionomer resin is reduced to a level at which the formation of a foam layer by expansion and foaming occurs in a desired state, the melt viscosity of the ionomer resin increases.

[0055] In the coextrusion lamination of the polyethylene resin layer and the foam layer containing the ionomer resin, it is important that the melt for forming the foam layer should be adjusted to the coextrusion temperature, at which the foaming of the melt is properly carried out. It is thus concluded that the temperature of the melt containing the ionomer resin is reduced, and the melt viscosity of the ionomer resin increases. As a result, the ionomer resin cannot be easily dispersed in the polyethylene resin matrix. That is, it has been difficult to produce a laminated foam sheet with desired antistatic properties in a stable manner so far. When the ionomer resin has a low melt flow rate, this becomes particularly significant.

[0056] On the other hand, in the method of the present invention, a mixed plasticizer containing component (A) is added to the second melt for forming the antistatic layer, and the component (A) is a specific alcohol with a high plasticizing effect for the ionomer resin. Therefore, even when the extrusion temperature of the second melt for forming the antistatic layer is low so as to match the extrusion temperature of the first melt for forming the foam layer, the melt viscosity of the ionomer resin can also be maintained at a low level. Even when the ionomer resin has a low melt flow rate, the plasticizing effect of component (A) is also reachable.

[0057] In addition, the volatile plasticizer further contains a component (B) showing a high plasticizing effect on the polyethylene-based resin (PE-2). Therefore, even when the extrusion temperature of the second melt for forming the antistatic layer is made low so as to match the extrusion temperature (usually 100 to 140° C.) of the first melt for forming the foam layer, the melt viscosity of the second melt as a whole can be maintained at a low level.

[0058] It is believed that, for the reasons described above, the method of the present invention can form in a stable manner a laminated foam sheet having an antistatic layer laminated on at least one side of a foam layer and in which an ionomer resin is uniformly dispersed in a polyethylene-based resin (PE-2) to form a conductive network structure showing improved antistatic properties.

[0059] Component (A) of the volatile plasticizer is an alcohol having a boiling point of 120° C. or lower. Examples of the alcohol include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, 2-butanol and 2-methyl-2-propanol. These alcohols can be used alone or in a mixture of two or more thereof. Ethanol or a mixture of ethanol and one or more alcohols is particularly preferred because it can significantly reduce the melt viscosity of the ionomer resin and it is easy to handle during the manufacture of the laminated foam sheet. It is therefore preferred that component (A) contains ethanol in an amount of 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably 80% by weight or more, based on the weight of component (A).

[0060] The alcohol of component (A) must have a boiling point of 120° C. or lower so that once the laminated foam sheet has been produced, the alcohol disappears rapidly from the antistatic layer and does not remain therein. From this viewpoint, the boiling point of the alcohol is preferably 100° C. or lower, more preferably 90° C. or lower, particularly preferably 85° C. or lower. For ease of handling, the lower limit of the boiling point of the alcohol is preferably 40° C., more preferably 50° C.

[0061] Component (B) of volatile plasticizer is selected from at least one of the following: saturated hydrocarbons with 3 to 5 carbon atoms, and dialkyl ethers in which the alkyl groups each have 1 to 3 carbon atoms. Specific examples of saturated hydrocarbons with 3 to 5 carbon atoms include propane, n-butane, isobutane, n-pentane and isopentane. It is particularly preferred to use n-butane, isobutane or a mixture thereof, because it has an excellent plasticizing effect on the polyethylene-based resin (PE-2), and it can effectively reduce the melt viscosity of the polyethylene-based resin (PE-2) during the coextrusion lamination process. When n-butane and isobutane are used in a mixture, the mixing ratio is not particularly limited. However, the mixing ratio of n-butane to isobutane is preferably 50:50 to 90:10, more preferably 60:40 to 80:20.

[0062] Examples of dialkyl ethers in which the alkyl groups each have 1 to 3 carbon atoms include dimethyl ether, diethyl ether, dipropyl ether and methyl ethyl ether. Dimethyl ether is particularly preferred because it has an excellent plasticizing effect on the polyethylene-based resin (PE-2) and can effectively reduce the melt viscosity of the polyethylene-based resin (PE-2) during the coextrusion lamination process.

[0063] Importantly, the volatile plasticizer should be present in the second melt in an amount of 0.1 to 10 moles per kilogram of the total weight of the polyethylene-based resin (PE-2) and the ionomer resin. When the amount of the volatile plasticizer is lower than the above range, the second melt cannot be fully plasticized, and its melt viscosity cannot be fully reduced. As a result, it becomes difficult to properly disperse the ionomer resin in the polyethylene-based resin (PE-2). In addition, due to the film-forming failure and stretching failure of the second melt, a uniform antistatic layer may not be obtained. From this viewpoint, the lower limit of the amount of the volatile plasticizer is preferably 0.5 moles, more preferably 1 mole, more preferably 1.5 moles, and particularly preferably 2 moles per kilogram of the total weight of the polyethylene-based resin (PE-2) and the ionomer resin. On the other hand, an excessively high amount of volatile plasticizer beyond the above range often causes the plasticizer to separate from the second melt, spray out from the die head, and the lamination failure of the antistatic layer on the foam layer. From this viewpoint, the upper limit of the amount of the volatile plasticizer is preferably 9 mol, more preferably 8 mol, particularly preferably 7 mol per kg of the total weight of the polyethylene-based resin (PE-2) and the ionomer resin.

[0064] It is also important that the molar ratio (A / B) of component (A) and component (B) should be 5:95 to 95:5, so as to plasticize both the polyethylene-based resin (PE-2) and the ionomer resin. When the molar ratio (A / B) is less than the above range, the ionomer resin cannot be plasticized, thereby the required antistatic properties cannot be obtained. Excessive molar ratio (A / B) causes the failure of plasticizing the polyethylene-based resin (PE-2), thereby a uniform antistatic layer cannot be obtained. For this reason and because the ionomer resin of a lower content obtains a better laminated foam sheet in a stable manner, the molar ratio (A / B) is preferably 6:94 to 80:20, more preferably 8:92 to 70:30, still more preferably 9:91 to 60:40, particularly preferably 10:90 to 50:50.

[0065] In order to appropriately plasticize the ionomer resin, the melt viscosity of the ionomer resin can be adjusted within a range suitable for extrusion molding, and in addition the ionomer resin can be dispersed in the polyethylene-based resin (PE-2) in a state that enables the formation of a desired antistatic network structure, it is preferred that component (A) is present in the second melt in an amount of 1 to 25 mol per kg of the ionomer resin. From this viewpoint, the lower limit of the amount of component (A) is preferably 2 mol, more preferably 3 mol, still more preferably 4 mol, particularly preferably 6 mol per kg of the ionomer resin, and the upper limit is preferably 24 mol, more preferably 22 mol, particularly preferably 20 mol per kg of the ionomer resin.

[0066] In the method of the present invention, the above-mentioned first melt and second melt are introduced into the independent passage of the die head and merged, so that the flow of the second melt for forming the antistatic layer is laminated on one side or both sides of the flow of the first melt for forming the foam layer. The merged flow is then coextruded and discharged through the die head into a lower pressure environment, usually discharged into the atmosphere, to obtain a laminated foam sheet, which consists of a foam layer and one or two antistatic layers laminated on one side or both sides of the foam layer and shows a close bond between adjacent layers.

[0067] Coextrusion foaming process includes two different methods. One method uses a flat coextrusion die, through which a sheet-like laminate is extruded and foamed to obtain an expected laminated foam sheet. Another method uses a round die, through which a tubular laminate is extruded and foamed. The tubular extruded laminate is then drawn and expanded by a mandrel, and cut to obtain an expected laminated foam sheet. Among these methods, the method of a round die is preferably used because it is easy to produce a wide laminated foam sheet with a width (lateral length) of 1,000 mm or more.

[0068] In a preferred method of producing laminated foam sheet by coextrusion foaming process using round die, polyethylene-based resin (PE-1) and (if necessary) one or more additives (such as cell control agent) are fed into the first extruder and heated and kneaded, and physical foaming agent is injected therein. Further kneading obtained mixture to obtain the first melt for forming foam layer. Meanwhile, polyethylene-based resin (PE-2), ionomer resin as polymer antistatic agent and (if necessary) one or more additives are fed into the second extruder and heated and kneaded, and volatile plasticizer is injected therein. Further kneading obtained mixture to obtain the second melt for forming antistatic layer. The first melt thus obtained and the second melt are fed into the round coextrusion die and merged. Then the merged logistics is coextruded into the atmosphere by the die, and it is foamed and expanded. Then the tubular extruded laminate is drawn and expanded by mandrel, and cut to obtain expected laminated foam sheet.

[0069] One or more additives can be included in the second melt for forming the antistatic layer with the degree that can not adversely affect the purpose of the present invention.The example of additive comprises antioxidant, heat stabilizer, weathering stabilizer, UV absorber, flame retardant, filler and antibacterial agent.The addition of one or more additives can be suitably determined according to its purpose and effect, but is preferably based on the second melt of 100 weight parts 10 weight parts or less, more preferably 5 weight parts or less, more preferably 3 weight parts or less.

[0070] The physical foaming agent incorporated into the first melt for forming the foam layer may be an organic or inorganic physical foaming agent. As an organic physical foaming agent, there may be mentioned, for example, aliphatic hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, n-hexane and isohexane; alicyclic hydrocarbons such as cyclopentane and cyclohexane; chlorinated hydrocarbons such as methyl chloride and ethyl chloride; fluorocarbons such as 1,1,1,2-tetrafluoroethane and 1,1-difluoroethane. As an inorganic physical foaming agent, there may be mentioned, for example, nitrogen, carbon dioxide, air and water. These physical foaming agents may be used in the form of a mixture of two or more thereof. If necessary, a decomposition type foaming agent such as azodicarbonamide may be used. Due to the compatibility and foaming properties of organic physical foaming agents with polyethylene-based resins (PE-1), organic physical foaming agents are particularly preferred, particularly those containing n-butane, isobutane or a mixture thereof as their main components. When n-butane and isobutane are used in the form of a mixture, the mixing ratio is not particularly limited. However, the mixing ratio of n-butane to isobutane is preferably 50:50 to 90:10, more preferably 60:40 to 80:20.

[0071] The amount of the foaming agent added is controlled according to the kind of the foaming agent and the expected apparent density of the laminated foam sheet. When butane or mixed butane is used as the physical foaming agent, for example, the amount thereof added is preferably 3 to 30 wt%, more preferably 4 to 20 wt%, more preferably 6 to 18 wt%, based on 100 wt% of the polyethylene-based resin (PE-1).

[0072] Among the additives optionally added to the first melt for forming the foam layer, the cell control agent is important. Inorganic or organic materials can be used as cell control agents. Examples of inorganic cell control agents include metal salts of boric acid (such as zinc borate, magnesium borate and borax), sodium chloride, aluminum hydroxide, talc, zeolite, silicon dioxide, calcium carbonate and sodium bicarbonate. Examples of organic cell control agents include 2,2-methylene-bis (4,6-di-tert-butylphenyl) sodium phosphate, sodium benzoate, calcium benzoate, aluminum benzoate and sodium stearate. Also useful as cell control agents are sodium bicarbonate-citric acid types, which use, for example, a combination of sodium bicarbonate and citric acid or a combination of sodium bicarbonate and an alkali metal salt of citric acid. These cell control agents can be used alone or in combination of two or more thereof. The addition amount of the cell control agent is adjusted according to the expected cell diameter.

[0073] Next, preferred physical properties and preferred morphology of the laminated foam sheet obtained by the method of the present invention will be described.

[0074] The laminated foam sheet preferably has two antistatic layers disposed on both sides of the foam layer, especially when used as an interlayer sheet to be inserted between articles (such as glass plates). The thickness (total thickness) of the laminated foam sheet is preferably 0.05 to 2 mm, so as to improve the loading efficiency when transporting articles with the laminated foam sheet inserted therebetween. From this point of view, the upper limit of the thickness is more preferably 1.5 mm, more preferably 1.2 mm, and particularly preferably 1.0 mm. In order to ensure its required cushioning properties, the lower limit of the thickness of the laminated foam sheet is preferably 0.1 mm, more preferably 0.2 mm, and particularly preferably 0.3 mm.

[0075] The laminated foam sheet preferably has a density of 20 to 200 kg / m 3 , more preferably 30 to 150 kg / m 3 , and more preferably 50 to 120 kg / m 3 The apparent density of the laminated sheet is preferably 10 to 200 g / m due to its good balance between light weight, handleability and cushioning properties. For the same reason, the basis weight of the laminated sheet is preferably 10 to 200 g / m 2 , more preferably 15 to 100 g / m 2 , and more preferably 20 to 80 g / m 2 .

[0076] From the standpoint of cost, light weight, and maintaining the desired antistatic properties, it is also preferred that the antistatic layer (or each of the two antistatic layers) have a thickness of 50 g / m 2 or lower, more preferably 40g / m 2 Lower, more preferably 30g / m 2 or lower, still more preferably 20 g / m 2 or lower, further preferably 10 g / m 2 or lower, particularly preferably 5g / m 2 In order to improve the layering efficiency, the lower limit of the basis weight Bw is preferably 1 g / m 2 , particularly preferably 1.5 g / m 2 .

[0077] The thickness of laminated foam sheet and antistatic layer can be determined as follows.Laminated foam sheet is cut vertically (in thickness direction) along its transverse direction (direction perpendicular to extrusion direction), and the photo of vertical cross section is taken at ten laterally spaced positions.On each of ten photos (enlarged), measure the thickness of antistatic layer and laminated foam sheet.Calculate the arithmetic mean of ten measured thickness values ​​of antistatic layer and the arithmetic mean of ten measured thickness values ​​of laminated foam sheet.At three randomly selected positions of total laminated foam sheet, repeat the above measurement and calculation.The arithmetic mean of the calculated values ​​in three positions represents the thickness of antistatic layer and laminated sheet.

[0078] The basis weight of the laminated foam sheet is measured as follows. The laminated foam sheet is cut vertically in the transverse direction to obtain a test piece, the width of which is, for example, 100 mm and the length of which is equal to the transverse length of the laminated foam sheet. The weight of the test piece is measured [g]. The measured weight is divided by its area [m 2 ] to obtain the basis weight of the specimen [g / m 2 ]. Apparent density of laminated foam sheet [kg / m 3 ] by its basis weight [kg / m 2 ] divided by the thickness of the test piece [m] (with appropriate unit conversion).

[0079] Basis weight of antistatic layer [kg / m 2 ] is calculated by multiplying its thickness by the density of its resin composition with appropriate unit conversion. As used herein, the term "resin composition" is intended to include not only ethylene-based resins (PE-2) and ionomer resins, but also other polymer components and inorganic components optionally used in the antistatic layer.

[0080] Alternatively, the basis weight of the antistatic layer can also be determined based on its extrusion rate. More specifically, the basis weight Bw [g / m 2 ] can be calculated by the following formula:

[0081] Bw=[1000X / (L×W)]

[0082] Wherein X represents the extrusion rate of the antistatic layer [kg / h], L represents the drawing rate of the laminated foam sheet [m / h], and W represents the width (lateral length) of the laminated foam sheet [m].

[0083] Furthermore, when the basis weight of the laminated foam sheet and the ratio of the extrusion rate of the antistatic layer relative to the extrusion rate of the foam layer are known, the basis weight of the antistatic layer can be determined by simple calculation.

[0084] In order for the laminated foam sheet to exhibit excellent antistatic properties and the effect of preventing dust accumulation, the antistatic layer of the laminated foam sheet preferably has a 1×10 13 Ω or less, more preferably less than 5×10 12 Ω, particularly preferably 1×10 12 The lower limit of the surface resistivity is not particularly limited, but is generally about 1×10 7 As long as the above-mentioned surface resistivity can be achieved, one or both sides of the antistatic layer may be further covered with a surface layer substantially free of a polymer antistatic agent.

[0085] The surface resistivity of the antistatic layer was measured according to JIS K6271 (2001). More specifically, a test piece (100 mm in length, 100 mm in width, and a thickness equal to the thickness of the laminated foam sheet to be measured) was cut out from the laminated foam sheet. Then, a voltage of 500 V was applied to the test piece, and the surface resistivity [Ω] of the antistatic layer was measured 1 minute after the start of the voltage application.

[0086] The present invention also provides a laminated foam sheet having a specific morphology produced by the above method of the present invention. The laminated foam sheet has an antistatic layer which is provided on one or both sides of the foam layer and contains a polyethylene-based resin (PE-2) and an ionomer resin as a polymer antistatic agent.

[0087] In the antistatic layer, the polyethylene-based resin (PE-2) forms a continuous phase (sea), and the ionomer resin forms a dispersed phase (island) dispersed in the continuous phase. Since the polyethylene-based resin (PE-2) forms a continuous phase, the antistatic layer shows excellent flexibility and cushioning properties. In addition, although the ionomer resin is used as a polymer antistatic agent, since the ionomer resin forms a dispersed phase, it is stretched in a stripe form to form a conductive network, so the foam sheet shows excellent antistatic properties.

[0088] The antistatic layer of the laminated foam sheet according to the present invention has a morphology such that the dispersed phase of the ionomer resin is small in size and stretched to a certain extent. The morphology is represented by the base median S 50 and LM 50 / LT 50 These parameters are described in detail below.

[0089] The number-based median S of the cross-sectional area of ​​the dispersed phase of the laminated foam sheet related to the size of the dispersed phase 50 Should be 1×10 2 Up to 1×10 6 nm 2 . Base median cross-sectional area S 50 It is the cross-sectional area of ​​the dispersed phase located in the middle (at 50% of the cumulative number) of the total number of dispersed phases arranged in the order of the size of the dispersed phase. The cross-sectional area of ​​the dispersed phase is measured on a perpendicular (thickness direction) cross section of the antistatic layer taken along the extrusion direction (machine direction or perpendicular to the transverse and longitudinal directions) of the laminated foam sheet. The median cross-sectional area S can be obtained by the number base 50 To evaluate the contribution of the ionomer resin dispersion to the antistatic performance of the antistatic layer.

[0090] More specifically, when S 50 1×10 2 Up to 1×10 6 nm 2When the small-sized ionomer dispersed phase is dispersed in a significant proportion in the polyethylene-based resin (PE-2) matrix. Such small S 50 . Too small S below the above range 50 On the other hand, when S 50 When the above range is exceeded, the dispersed phase cannot be properly dispersed in the matrix resin, and the desired antistatic properties cannot be obtained. From the above viewpoint, the lower limit is preferably 5×10 2 nm 2 , more preferably 1×10 3 nm 2 , and the upper limit is preferably 1×10 5 nm 2 , more preferably 5×10 4 nm 2 .

[0091] In addition to the above S 50 In addition, the LM 50 / LT 50 The ratio is also important to obtain the desired antistatic properties. 50 / LT 50 The ratio is the median value of the diameter of the dispersed phase in the extrusion direction LM 50 The median value of the diameter of the dispersed phase in the thickness direction LT 50 ratio and should be 2 or higher. 50 / LT 50 When the ratio is 2 or more, the dispersed phases are each stretched in the form of stripes, thereby forming a desired antistatic network structure.

[0092] The median value of the diameter of the dispersed phase in the extrusion direction is LM 50 and the median of the diameter of the dispersed phase in the thickness direction LT 50 It can be determined as follows. Take a vertical section of the antistatic layer along the extrusion direction of the laminated foam sheet. On the vertical section, measure the Feret diameter of the dispersed phase in both the extrusion direction and the thickness direction. The number-based median diameter LM of the dispersed phase 50 is the Feret diameter of the dispersed phase in the extrusion direction that is located in the middle (at 50% of the cumulative number) of the total number of dispersed phases arranged in order of their Feret diameters. Similarly, the number-based median diameter LT of the dispersed phase 50 It is the Feret's diameter in the thickness direction of the dispersed phase located in the middle (at 50% of the cumulative number) of the total number of dispersed phases arranged in the order of their Feret's diameters.

[0093] LM 50 / LT 50The fact that the ratio is 2 or more indicates that the dispersed phase is stretched in the extrusion direction. Therefore, the dispersed ionomer resin is promoted to form a conductive network structure, and thus the antistatic layer shows improved antistatic properties. Too small LM below the above range 50 / LT 50 The ratio is not enough to form the antistatic network structure required to obtain the desired antistatic properties. From this point of view, LM 50 / LT 50 The ratio is preferably 3 or more. In order to achieve the desired antistatic properties in a stable manner, LM 50 / LT 50 The upper limit of the ratio is generally about 20, preferably 10, and more preferably 6.

[0094] In the case of satisfying the above-mentioned median area S 50 and diameter ratio LM 50 / LT 50 In the antistatic layer of the laminated foam sheet with specific requirements, the dispersed phase size of the ionomer resin is small and stretched to a certain extent. Therefore, the laminated foam sheet shows excellent antistatic properties, such as 1×10 12 Ω or lower surface resistivity. In addition, the use of ionomer resins as antistatic agents can reduce contamination of articles that remain in direct contact with the laminated foam sheet.

[0095] In order to obtain a laminated foam sheet having excellent antistatic properties in a stable manner, it is preferred that the number-based median value LT of the diameter of the dispersed phase in the thickness direction is 50 It is 10 to 1,000 nm, more preferably 15 to 600 nm, still more preferably 20 to 500 nm, particularly preferably 30 to 300 nm.

[0096] In order to easily obtain the desired antistatic properties, it is also preferred that at least one dispersed phase (island) of the ionomer resin is present on average on a line segment extending through the entire antistatic layer in the vertical (thickness) direction of the antistatic layer. From this viewpoint, the average number NT of the dispersed phase on such a vertical line segment is more preferably 2 or higher, particularly preferably 5 or higher. The upper limit of the average number NT is usually about 100, more preferably 30, and particularly preferably 20.

[0097] The average number NT is determined as follows. At six arbitrarily selected positions spaced apart laterally from each other, six cross-sectional images of the antistatic layer are taken along its extrusion direction. Then, on each of the six cross-sectional images, five vertical lines separated by 2 μm intervals are drawn through the thickness of the entire antistatic layer. The number of dispersed phases intersecting with the vertical line segments is counted. The sum of the counts is divided by the number of line segments (30 (6 images × 5 positions)) to obtain the average number NT of the dispersed phases intersecting with the vertical line segments extending between the two sides of the antistatic layer.

[0098] In order to determine the above-mentioned area median value S of the ionomer resin dispersed phase in the antistatic layer of the laminated foam sheet 50 , diameter ratio LM 50 / LT 50 For each of the average number NT and the average number NT, the laminated foam sheet is cut in a perpendicular direction along its extrusion direction to obtain a test piece having a vertical cross section of the laminated foam sheet in the form of a film. The film is then dyed and measured by a transmission electron microscope to obtain a cross-sectional image. On the obtained image, the morphology of the dispersed phase is measured in the above manner. The method for measuring the morphology will be described in more detail below in the examples of the present invention.

[0099] The laminated foam sheet obtained by the method of the present invention can be used as, for example, an interlayer sheet and a cushioning or packaging material for electronic devices. The laminated foam sheet can be particularly used as an interlayer sheet inserted between glass substrates used as glass panels for various image display devices such as liquid crystal displays, plasma displays, and electroluminescent displays.

[0100] The following examples and comparative examples will further illustrate the present invention. The polyethylene-based resin, ionomer resin polymer antistatic agent, foaming agent, volatile plasticizer and cell control agent used in Examples 1 to 11 and Comparative Examples 1 to 4 are given below.

[0101] (1) Polyethylene-based resins (PE-1 and PE-2):

[0102] Low-density polyethylene (trade name "NUC8009", manufactured by NUC Corporation), density: 917 kg / m 3 , MFR: 9.0g / 10min, melting point: 107℃;

[0103] (2) Ionomer resin (polymer antistatic agent):

[0104] Potassium ionomer resin (trade name "ENTIRA MK400", manufactured by duPont-Mitsui Polychemicals Co., Ltd.), density: 970 kg / m 3 , MFR: 1.5g / 10min, melting point: 93℃, surface resistivity: 1.0×10 7 Ω;

[0105] (3) Physical foaming agent:

[0106] A butane mixture consisting of 65% by weight of n-butane and 35% by weight of isobutane;

[0107] (4) Volatile plasticizer (blend of components (A) and (B)):

[0108] Component (A): ethanol (trade name "ETHANOL (99.5)", manufactured by Kanto Chemical Co., Inc.);

[0109] Component (A): an alcohol mixture (trade name "MIX ETHANOL NP", manufactured by Yamaichi Chemical Industries Co., Ltd.), a blend of 85.5 wt% of ethanol, 4.9 wt% of isopropanol and 9.6 wt% of n-propanol;

[0110] Component (B): a mixed butane consisting of 65 wt% n-butane and 35 wt% isobutane;

[0111] Component (B): dimethyl ether;

[0112] (5) Cell control agent:

[0113] A blend of citric acid and sodium bicarbonate (product name: PO-217K, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.).

[0114] The device for forming the laminated foam sheet of embodiment 1 to 11 and comparative example 1 to 4 is as follows.In order to form the foam layer, a series extruder is used, which has an internal diameter of 90mm for the first extruder and an internal diameter of 120mm for the second extruder connected in series with the downstream side of the first extruder.In order to form the antistatic layer, an internal diameter of 50mm for the third extruder is used.In order to form the laminated foam sheet, an external diameter of 94mm for coextrusion circular die is used.The circular die is provided with an independent tubular passage, which is constructed so that the melt for forming the antistatic layer merges with the inboard and the outside of the tubular flow of the melt for forming the foam layer and is laminated thereon.

[0115] Example 1

[0116] 100 parts by weight of polyethylene-based resin PE-1 and 1.6 parts by weight of cell control agent per 100 parts by weight of PE-1 were supplied to the first extruder. The feed was melted and kneaded at about 200° C. in the first extruder, and a physical foaming agent was injected therein in an amount of 12 parts by weight per 100 parts by weight of polyethylene-based resin PE-1 and kneaded together. The kneaded material was then fed to a second extruder connected downstream of the first extruder, and the resin temperature was adjusted to about 112° C. to obtain a melt for forming a foam layer.

[0117] Meanwhile, polyethylene-based resin PE-2 (same as PE-1) and ionomer resin were supplied to the third extruder, and then melted and kneaded at a temperature of about 200° C. Thereafter, a volatile plasticizer having a composition shown in Table 1-1 was injected into the kneaded material in the third extruder in an amount shown in Table 1-1 and kneaded together, and the resin temperature was adjusted to about 120° C. to obtain a melt for forming an antistatic layer. The addition amount of the ionomer resin (expressed as weight % based on the total weight (100 weight %) of the ionomer resin and the polyethylene-based resin PE-2), the molar amount of component (A) (ethanol) per kg of the total weight of the ionomer resin and the polyethylene-based resin PE-2, the molar amount of component (A) (ethanol) per kg of the ionomer resin, the molar amount of component (B) (mixed butanes) per kg of the total amount of the ionomer resin and the polyethylene-based resin PE-2, the molar amount of the volatile plasticizer per kg of the total amount of the ionomer resin and the polyethylene-based resin PE-2, and the molar ratio of component (A) to component (B) are summarized in Table 1-1.

[0118] The melt for forming foam layer and antistatic layer thus prepared is fed to the coextrusion circular die head with the following discharge rate (extrusion rate) from respective extruders: 60kg / hour in the case of the melt for forming foam layer, and 5kg / hour in the case of each antistatic layer. The feeding in the circular die head is merged so that two tubular streams of the melt for forming antistatic layer are laminated on the inner side and the outer side of the tubular stream of the melt for forming foam layer respectively. Then the merged stream is coextruded and discharged into the atmosphere by the coextrusion die head, to obtain the tubular laminated foam product with three-layer structure. The tubular laminated material foam product is drawn while the mandrel is expanded by an external diameter of 350mm, and is cut in the extrusion direction, to obtain the laminated foam sheet material with a width of about 1000mm. The drawing rate of the tubular laminated material is adjusted so that the basis weight of the laminated foam sheet material is as shown in Table 2. The thickness and apparent density of the laminated foam sheet and the basis weights of the foam layer and the antistatic layer (one antistatic layer) of the laminated foam sheet are also shown in Table 2.

[0119]

[0120]

[0121] Examples 2 to 8

[0122] Example 1 was repeated in the same manner as described above to obtain a laminated foam sheet, except that the ratio of the ionomer resin to the polyethylene-based resin PE-2 (in Examples 7 and 8), the composition of the volatile plasticizer, and the amount of the volatile plasticizer were changed as shown in Tables 1-1 and 1-2. The drawing rate of each tubular laminate was adjusted so that the basis weight of each laminated foam sheet was as shown in Table 2. The thickness and apparent density of each laminated foam sheet and the basis weight of the foam layer and the antistatic layer (each antistatic layer) of each laminated foam sheet are also shown in Table 2.

[0123] Comparative Examples 1 and 2

[0124] Example 1 was repeated in the same manner as described above, except that component (A) was not used and the composition and amount of the volatile plasticizer were changed as shown in Table 1-2, to obtain a laminated foam sheet.

[0125] The physical properties of the laminated foam sheet thus obtained are summarized in Table 2.

[0126]

[0127] In Table 2, the thickness, apparent density and basis weight of the laminated foam sheet, and the basis weights of the foam layer and the antistatic layer were measured by the above method. The basis weight of the antistatic layer was determined by calculation based on the basis weight of the laminated foam sheet and the ratio of the extrusion rate of the antistatic layer to the extrusion rate of the foam layer.

[0128] The surface resistivity of each antistatic layer disposed on both sides of the foam layer was determined by the following method. Three test pieces were cut out from randomly selected positions, each of which had a length of 100 mm, a width of 100 mm and a thickness equal to the thickness of the laminated foam sheet. Then, according to the method of JIS K6271 (2001), each test piece was placed in an environment at a temperature of 23° C. and a relative humidity of 50%, and a voltage of 500 V was applied. One minute after the start of voltage application, the surface resistivity of each test piece was measured. Measurements were made on each of the two surfaces of each of the three test pieces. The surface resistivity of each side of the laminated foam sheet is the arithmetic mean of the three measured values. Model TR8601 manufactured by Takeda Riken Industry Co., Ltd. was used as a measuring instrument. In Table 2, the "M side" is the side of the laminated foam sheet facing the mandrel during its manufacturing process, and the "S side" is the opposite side of the M side.

[0129] The antistatic properties of the laminated foam sheets were evaluated based on the following criteria:

[0130] Good: The surface resistivity of the antistatic layer is 1×10 13 Ω or lower.

[0131] Bad: The surface resistivity of the antistatic layer exceeds 1×10 13 Ω.

[0132] The results are shown in Table 2. The laminated foam sheets of Comparative Examples 1 and 2 did not show antistatic properties.

[0133] Examples 9 to 11

[0134] Example 1 was repeated in the same manner as described above, except that the cell control agent was supplied to the first extruder in an amount of 2 parts by weight per 100 parts by weight of the polyethylene-based resin PE-1 and the composition of the volatile plasticizer and the amount of the volatile plasticizer were changed as shown in Table 3, to obtain a laminated foam sheet.

[0135] Comparative Examples 3 and 4

[0136] Example 9 was repeated in the same manner as described above, except that the composition of the volatile plasticizer and the amount of the volatile plasticizer were changed as shown in Table 3, to obtain a laminated foam sheet.

[0137] The physical property (thickness, basis weight and apparent density of the laminated foam sheet obtained in embodiment 9 to 11 and comparative examples 3 and 4) and the basis weight of its antistatic layer (an antistatic layer) are measured in the same manner as above. In addition, the form of the antistatic layer (S side) is analyzed to provide the result shown in Table 4. The antistatic property of the laminated foam sheet and the property of preventing the transfer (preventing the property of low molecular weight substances from transferring from the laminated foam sheet) are also measured to provide the result shown in Table 5. Form is measured and the property of preventing the transfer is prevented by the method described hereinafter. The measurement of the surface resistivity of the antistatic layer and the evaluation of the antistatic property of the laminated foam sheet are carried out in the same manner as above.

[0138]

[0139]

[0140] Table 5

[0141]

[0142] Measure S in Table 4 50 LM 50 and LT 50 Method:

[0143] In the transverse direction including laminated foam sheet near the center and the three positions of both sides end, the laminated foam sheet is cut in the vertical direction along its extrusion direction to obtain three test pieces of the vertical section with laminated foam sheet respectively. Three test pieces are cut separately to obtain the ultrathin film with vertical section. Then each film is dyed with ruthenium tetroxide, so that the resin phase based on polyethylene can be distinguished from the ionomer resin phase by light tone and dark tone. Using transmission electron microscope (JEM-1400Plus manufactured by JEOL Ltd.), under the accelerating voltage of 100kV and under the magnification of 7,000 times and 70,000 times, the dyeing section of each film is observed and measured to obtain a cross-sectional image. Figure 1 and Figure 2 are transmission electron micrographs of the antistatic layer of Example 9 at magnifications of 7,000 and 70,000, respectively, and Figure 3 is a similar transmission electron micrograph of the antistatic layer of Comparative Example 3 at a magnification of 7,000. Figures 1 to 3 In the figure, the dark and light parts show the ionomer resin phase and the polyethylene-based resin phase, respectively.

[0144] The cross-sectional photographs were pre-processed so that the dispersed phase was distinguished from the other phases (continuous phase) by a black-and-white pattern based on the contrast and the presence of a lamellar structure. Because the ionomer resin has a higher amorphous content than the polyethylene-based resin, the dispersed phase can be regarded as a region lacking a lamellar structure compared to the continuous phase in the cross-sectional photographs. The boundary portion between the continuous phase and the dispersed phase is included in the dispersed phase. Then, the pre-processed cross-sectional photographs were analyzed with an image processing software (NonoHunter NS2K-Pro manufactured by Nanosystem Co., Ltd.) under the following conditions:

[0145] (1) Monochrome conversion

[0146] (2) Smoothing filter (processing time: 1 to 10)

[0147] (3) Binarization by NS method (sharpness: 41, sensitivity: 10, denoising, concentration range: 45 to 255)

[0148] (4) Feret diameter and area measurement

[0149] In the measurement under the above conditions (1) to (4), the total area of ​​the selected region is at least 100 μm 2 The measurement area is randomly selected from the cross section of the antistatic layer in a manner.

[0150] The number-based median S of the cross-sectional area of ​​the dispersed phase in the antistatic layer is measured as follows 50. Measure the number and cross-sectional area of ​​all dispersed phases in the selected area. Those dispersed phases that intersect the boundary of the selected area are included in the measurement. 2 Those dispersed phases that are smaller than 100 μm are excluded from the measurement. The black part (such as the wrinkles and / or the outermost part of the film) that is not classified as dispersed phase is also excluded from the measurement. Each of the above three test pieces is measured. By the number of dispersed phases measured in the three test pieces and the cross-sectional area of ​​the dispersed phase, the number base median S of the cross-sectional area of ​​the dispersed phase of the antistatic layer is determined. 50 . Base median cross-sectional area S 50 It is the cross-sectional area of ​​the dispersed phase at 50% of the cumulative number of dispersed phases arranged in order of size of the dispersed phases.

[0151] The number-based median LM of the diameter of the dispersed phase in the extrusion direction is determined as follows 50 and the median of the diameter of the dispersed phase in the thickness direction LT 50 Under the above conditions (1) to (4), the Feret diameter of the dispersed phase in both the extrusion direction and the thickness direction on the cross-sectional photograph is measured. Those dispersed phases that intersect the boundary of the selected area are included in the measurement. The measurement is performed for each of the above three specimens. From the amount of dispersed phase measured in the three specimens and the Feret diameter of the dispersed phase in both the extrusion direction and the thickness direction, LM is determined. 50 and LT 50 LM, the number-based median diameter of the dispersed phase 50 is the Feret diameter of the dispersed phase in the extrusion direction at 50% of the cumulative number of dispersed phases arranged in the order of Feret diameter of the dispersed phase, and the number-based median diameter LT of the dispersed phase 50 is the Feret diameter of the dispersed phase in the thickness direction at 50% of the cumulative amount.

[0152] The measurement method of NT in Table 4 is:

[0153] The average number NT of dispersed phases intersecting a vertical line segment extending between the two sides of the antistatic layer is determined by the method described previously.

[0154] Table 5: Measurement method for preventing transfer properties:

[0155] A pre-cleaned slide glass manufactured by Matsunami Glass Industries, Ltd. was used as a material in direct contact with the laminated foam sheet. Ten slide glass sheets were stacked on top of each other to obtain a stack of ten glass sheets. The haze value (H0 [%]) of the stack in the thickness direction (stacking direction) of the laminate was measured using a haze meter (Model NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.). Next, one side of each of the ten similar slide glass sheets was irradiated with 3.8 g / cm 2 The laminated foam sheet was pressed into contact with a pressure of , and then allowed to stand for 24 hours in an environment maintained at a temperature of 60°C and a relative humidity of 90%. Then, the laminated foam sheet was removed, and the remaining ten slides were stacked on each other. The haze value (H1[%]) of the glass stack was measured in the same manner as above. The difference (H1-H0) between the haze values ​​of the glass before and after contact with the laminated foam sheet was calculated. The smaller the difference (H1-H0), the less the low molecular weight substances contained in the antistatic agent in the laminated foam sheet are transferred to the slide. The transfer prevention property is evaluated as follows:

[0156] Good: The difference is 1.5% or less Bad: The difference is more than 1.5%.

Claims

1. An extrusion laminated foam sheet comprising a polyethylene-based resin foam layer and a polyethylene-based resin antistatic layer, the antistatic layer being laminated on at least one side of the foam layer, the antistatic layer containing a polyethylene-based resin (PE-2) and an ionomer resin as a polymer antistatic agent, and the antistatic layer having a 1×10 12 Ω or lower surface resistivity, wherein the polyethylene-based resin (PE-2) forms a continuous phase, and the ionomer resin forms a dispersed phase dispersed in the continuous phase, in, In a vertical cross section of the antistatic layer taken along the extrusion direction of the laminated foam sheet, the median value S of the cross-sectional area of ​​the dispersed phase is 50 1×10 2 Up to 1×10 6 nm 2 , the median value LM of the diameter of the dispersed phase in the extrusion direction 50 The median value of the diameter of the dispersed phase in the thickness direction is LT 50 The ratio LM 50 / LT 50 is 2 or more, and the average number NT of the dispersed phase intersecting a vertical line segment extending between both sides of the antistatic layer is 1 or more, and wherein the antistatic layer has a polystyrene-based resin content of 3 wt% or less based on the total weight of the polyethylene-based resin (PE-2) and the ionomer resin.

2. The extrusion laminated foam sheet according to claim 1, wherein the antistatic layer does not contain a polystyrene-based resin. 3 . The extruded laminated foam sheet according to claim 1 , wherein the ionomer resin has a melt flow rate of 3 g / 10 min or less at a temperature of 190° C. and a load of 2.16 kg.

4. The extruded laminated foam sheet according to claim 1 or 2, wherein the polyethylene-based resin (PE-2) has a melt flow rate of 1 to 20 g / 10 min at a temperature of 190°C and a load of 2.16 kg.

5. The extruded laminated foam sheet according to claim 1 or 2, wherein the laminated foam sheet has a density of 20 to 200 kg / m 3 The apparent density of .

6. The extruded laminated foam sheet according to claim 1 or 2, wherein the polyethylene-based resin (PE-2) has a melt flow rate (MFR) of E The melt flow rate MFR of the ionomer resin I The difference between E -MFR I ) is 5 to 20 g / 10 min.

7. The extruded laminated foam sheet according to claim 1 or 2, wherein the difference (Tmp-Tmi) between the melting point Tmp of the polyethylene-based resin (PE-2) and the melting point Tmi of the ionomer is 5 to 45°C.

8. The extruded laminated foam sheet according to claim 1 or 2, wherein the extruded laminated foam sheet is obtained by a method comprising the following steps: providing a first melt containing a polyethylene-based resin (PE-1) and a physical foaming agent, providing a second melt containing a polyethylene-based resin (PE-2), an ionomer resin as a polymeric antistatic agent, and a volatile plasticizer, and co-extruding the first melt and the second melt to form the laminated foam sheet, wherein the polyethylene-based resin foam layer and the polyethylene-based resin antistatic layer are formed from the first melt and the second melt, respectively, wherein the volatile plasticizer consists of a blend of component (A) and component (B), wherein component (A) is at least one alcohol having a boiling point of 120° C. or less, and component (B) is at least one selected from the group consisting of a saturated hydrocarbon having 3 to 5 carbon atoms, and a dialkyl ether in which each alkyl group has 1 to 3 carbon atoms, wherein the molar ratio of the component (A) to the component (B) is 5:95 to 95:5, and wherein the volatile plasticizer is present in the second melt in an amount of 0.1 to 10 moles per kilogram of the total weight of the polyethylene-based resin (PE-2) and the ionomer resin.

Citation Information

Patent Citations

  • Inter-lying paper for glass plate

    JP2016204227A

  • Laminated foam interleaf sheet for glass plates

    US20160311202A1